Solve the equation. \[ \frac{2 x}{x-2}=5+\frac{13 x^{2}}{x-2} \]
Solución de tutoría real
Responder
Solución
¡Inicia sesión para desbloquear respuestas gratis!
Una plataforma de aprendizaje en la que confían millones de estudiantes y profesores reales.
Revisado y aprobado por el equipo de tutoría de UpStudy
Bonus Knowledge
To solve the equation \[ \frac{2 x}{x-2}=5+\frac{13 x^{2}}{x-2}, \] let's start by getting rid of the denominator. Multiply both sides by \(x - 2\) (assuming \(x \neq 2\)): \[ 2x = 5(x - 2) + 13x^2. \] Now, distribute the \(5\) on the right side: \[ 2x = 5x - 10 + 13x^2. \] Next, rearrange the equation to get everything on one side: \[ 0 = 13x^2 + 5x - 10 - 2x, \] which simplifies to: \[ 0 = 13x^2 + 3x - 10. \] Now we can solve this quadratic equation using the quadratic formula: \[ x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a}, \] where \(a = 13\), \(b = 3\), and \(c = -10\). Calculate the discriminant: \[ b^2 - 4ac = 3^2 - 4 \cdot 13 \cdot (-10) = 9 + 520 = 529. \] Now substituting in the values: \[ x = \frac{-3 \pm \sqrt{529}}{2 \cdot 13} = \frac{-3 \pm 23}{26}. \] This gives us two potential solutions: \[ x = \frac{20}{26} = \frac{10}{13} \quad \text{and} \quad x = \frac{-26}{26} = -1. \] Thus, the solutions to the equation are: \[ \boxed{\frac{10}{13} \text{ and } -1}. \]